2009
DOI: 10.1074/jbc.m807398200
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Receptor Affinity of the Sialic Acid-binding Domain of Vibrio cholerae Sialidase through Multivalency

Abstract: Many glycoside hydrolases possess carbohydrate-binding modules (CBMs) that help target these enzymes to appropriate substrates and increase their catalytic efficiency. The Vibrio cholerae sialidase contains two CBMs, one of which is designated as a family CBM40 module and has been shown through structural and calorimetry studies to recognize the ␣-anomer of sialic acid with a K D of ϳ30 M at 37°C. The affinity of this V. cholerae CBM40 module for sialic acid is one of the highest reported for recognition of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…1B). Multivalency was achieved either through tandem repeats (17) or by fusing one or two tandemly linked CBM domains to an oligomerization domain (TD) derived from Pseudomonas aeruginosa sialidase (Fig. 1C) (19),…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). Multivalency was achieved either through tandem repeats (17) or by fusing one or two tandemly linked CBM domains to an oligomerization domain (TD) derived from Pseudomonas aeruginosa sialidase (Fig. 1C) (19),…”
Section: Resultsmentioning
confidence: 99%
“…1D and Table S2). Glycan array screening of VcCBM (17) and SpCBM (Fig. S1) showed that they recognize glycans containing terminal α-2,3-or α-2,6-linked sialic acids, and crystallographic analysis with bound sialyllactose reveals that only the terminal sialic acid interacts with each domain (18).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…For histopathological examination, an additional 2 mice from each group were sacrificed on days 0, 3, 6, and 9 p.i. Three weeks after the initial inoculation with A/Anhui/1/2013 (H7N9) influenza virus, the surviving mice received a second administration of Sp2CBMTD (10-g dose) once (day Ϫ7 or Ϫ3), twice (days Ϫ3 and Ϫ1), or three times (days Ϫ7, Ϫ3, and Ϫ1) prior to being reinfected with 20 were measured using a mouse MCYTOMAG-70K-PMX Milliplex premixed kit (Millipore), according to the manufacturer's instructions. For each cytokine, the standard curve ranged from 3.2 to 10,000 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…By using structural information, Connaris, Crocker, and Taylor (20) and Connaris et al (21) recently developed multivalent proteins based on SA-recognizing carbohydrate-binding modules (mCBMs) derived from bacterial sialidases with high affinity to SA receptors (Vc2CBMTD and Sp2CBMTD) (20,21 (21). The biologics appear to stimulate inflammatory mediators that confer protective ability in mice (21).…”
mentioning
confidence: 99%